Long-Term Suicide Risk of Children and Adolescents With Attention Deficit and Hyperactivity Disorder—A Systematic Review - Garas, Peter; Balazs, Judit (Frontiers in Psychiatry, 2020)
Background. Attention deficit and hyperactivity disorder (ADHD) is one of the most common mental disorders in childhood. Recently several studies showed the high suicide risk of patients with ADHD, however most of these studies had cross-sectional design. Aims. The aim of the current research is to complete a systematic review of the published studies which investigate the suicide risk of ADHD patients with longitudinal design. Methods. The systematic search was made on OVID Medline, PsychInfo, PubMed, Scopus, and Web of Science. The search terms were (ADHD OR attention deficit hyperactivity disorder) AND (suicide OR suicidal OR suicidality) AND (follow-up OR longitudinal study OR prospective study). Inclusion criteria were: written in English; participants under 18 years at the baseline; longitudinal, prospective studies; ADHD population at the baseline and at the follow-up; suicide behavior as primary outcome. Exclusion criteria were: the study did not contain empirical data, and reviews/meta-analyses and studies which aimed to investigate the drug treatment efficacy of ADHD. Results. After the screening process, 18 papers were included in the systematic review. The range of follow-up periods varied between 3.9 and 20.0 years. Several different assessment tools were used to investigate the symptoms and/or the diagnosis of ADHD and the suicidal risk. Eight studies enrolled children aged under 12 at baseline, six studies used birth cohort data. 17 studies found a positive association between ADHD diagnosis at baseline and the presence of suicidal behavior and/or attempts at the follow-up visits. Limitations. The main limitation of this review is the methodological heterogeneity of the selected studies. Further limitation is the relatively low number of studies with balanced gender ratios. Additionally, only one study published data about the treatment of ADHD. Finally, though we carefully choose the keywords, we still may be missing some relevant papers on this topic. Conclusions. In spite of the methodological diversity of the included studies, the results of the current systematic review highlight the importance of screening suicidality in the long term in patients with ADHD. Therefore, further studies are needed that compare the suicidal risk of treated and untreated groups of ADHD patients in the long-term.